2020
DOI: 10.1002/csr.2077
|View full text |Cite
|
Sign up to set email alerts
|

Corporate social responsibility, emotions, and consumer loyalty in the food retail context: Exploring the moderating effect of regional identity

Abstract: Corporate social responsibility (CSR) is presently one of the most interesting topics in the field of consumer behavior. However, not enough is known about the underlying mechanisms that explain how and when consumer CSR perceptions shape consumer behaviors such as loyalty. The present study proposes and demonstrates that CSR positively influences consumer loyalty through two mediators (how), which are gratitude ‐an emotion‐ and commitment ‐an attitude‐; regional identity is also introduced for the first time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 101 publications
(183 reference statements)
0
28
0
9
Order By: Relevance
“…More recently, Devin and Richards (2018) have concluded that CSR is being disclosed with different approaches throughout the food and beverage supply chain. Considering the social relevance of food and beverage sector, companies need to deepen their focus on what they are reporting and consider their customers' national and cultural characteristics in defining their disclosures (Fernández-Ferrín et al , 2020). Finally, according to Nirino et al (2019), the adoption of CSR at a governance level in the food sector has a strong impact on society and the environment, and a deeper understanding of food and beverage companies CSR strategy becomes necessary.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Devin and Richards (2018) have concluded that CSR is being disclosed with different approaches throughout the food and beverage supply chain. Considering the social relevance of food and beverage sector, companies need to deepen their focus on what they are reporting and consider their customers' national and cultural characteristics in defining their disclosures (Fernández-Ferrín et al , 2020). Finally, according to Nirino et al (2019), the adoption of CSR at a governance level in the food sector has a strong impact on society and the environment, and a deeper understanding of food and beverage companies CSR strategy becomes necessary.…”
Section: Introductionmentioning
confidence: 99%
“…This effect seems to be demonstrated in the work of Fernández-Ferrín et al (2021) on the effect of regional identity as a moderator/driver of the relationship between CSR and consumer loyalty, or in the study by Lantz and Loeb (1998) on the preference for consuming locally manufactured products. In this context, we suggest that politicians affiliated with a party that defends regionalist interests are likely to have a strong regional identity, which will lead them to promote policies that favor spending in that region through greater CSR.…”
Section: Regional Identity and Csrmentioning
confidence: 90%
“…Some well-known social identities in business studies include gender, age, race, culture, sexual orientation, and nationality (e.g., Markoczy et al 2020;Raskovic and Takacs-Haynes 2021). Although studies addressing political-territorial identification have focused primarily on national identity based on nationality (e.g., Kaczmarek et al 2012;Wöcke et al 2018), a growing body of work addresses regional identity, considering it as another form of subnational identity that focuses on the individual's relationship with their local/ regional community (Lantz and Loeb 1998;Fernández-Ferrín et al 2021). According to Raagmaa (2002, p. 58), who adapts the definition of Häuszer and Frey (1987), regional/local identity can be defined as "a phenomenon where people identify themselves with the social system of a certain region …with its people, culture, traditions, landscape, etc.".…”
Section: Regional Identity and Csrmentioning
confidence: 99%
See 1 more Smart Citation
“…Customers' purchase decisions are influenced by a company's CSR conduct (Fernández‐Ferrín et al, 2021). Most observers believe that “good firms” (those with a reputation for being socially responsible) will attract customers to their products, whereas “bad companies” (those that ignore their social responsibilities or cheat in their reporting) will be punished by customers—for example, through boycotts).…”
Section: Literature Reviewmentioning
confidence: 99%